PENERAPAN MODEL PEMBELAJARAN JIGSAW DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN FIKIH - Ida Husnal Choridah (MADRASCIENCE: Jurnal Pendidikan Islam, Sains, Sosial, dan Budaya, 2020)
The purpose of this study is to improve student learning outcomes in class XII IPS-1 MAN 1 Bandung City on the subject of Jurisprudence, Hajj and Umrah material. This type of research is a classroom action research conducted in two cycles, each of which is carried out in 2 meetings. Each meeting consists of the planning, action, observation, and reflection stages. The subjects in this study were all students of class XII IPS-1 MAN 1 Bandung in the odd semester of the 2018-2019 academic year totaling 35 students. Data obtained in this study include: learning outcomes and student learning completeness taken from the provision of test questions at the end of each meeting and student activity in the learning process takes place. From the research data obtained the average student learning outcomes in the first cycle was 78.57 and the second cycle was 96.00. The average mastery learning in the first cycle was 74.29% and the second cycle was 100%. From these data it is clear that from cycle I to cycle II there was a significant increase. From this study, it was concluded that by using a jigsaw cooperative learning model can improve student learning outcomes in class XII IPS-1 MAN 1 Bandung in the Subjects of Jurisprudence on Hajj and Umrah material.